The Relationship Between Interpersonal Communication of Guidance and Counseling Teachers and Trust in Problem Disclosure in Public High Schools in Banda Aceh City - Yahya, Martunis; Rosita, Dara; Riski, M. (Jurnal Suloh, 2024)
Communication helps build strong relationships between students and guidance and counseling teachers so that they can provide confidence in conveying their problems. This research aims to determine the relationship between guidance and counseling teachers' interpersonal communication with students' confidence in presenting problems at Banda Aceh City Public High Schools. This research uses a quantitative approach with a correlation research type. The population in this study were students of Banda Aceh City State High School with a sample of 687 students consisting of classes VII-VIII of Banda Aceh State High School 4 and Banda Aceh State High School 16 using the probability sampling method with cluster random sampling technique. Based on the research results, it shows that the degree of relationship (correlation) between the independent variable and the dependent variable is 44.8%, meaning that the interpersonal communication of guidance and counseling teachers at Banda Aceh City State High School has a moderate level relationship with trust in conveying student problems. If interpersonal communication is in the high category, then trust in conveying problems is also in the high category. The interpersonal communication relationship of guidance and counseling teachers has a significant effect on confidence in conveying problems to Banda Aceh City State High School students.Keywords: Interpersonal Communication, Trust in Conveying Problems.